2000
DOI: 10.1046/j.1365-3156.2000.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Crimean‐Congo haemorrhagic fever: a seroepidemiological and tick survey in the Sultanate of Oman

Abstract: SummaryIn 1995 and 1996, 4 persons from the Sultanate of Oman were confirmed with clinical Crimean-Congo haemorrhagic fever (CCHF). To assess the prevalence of CCHF virus infection in Oman, a convenience sample of imported and domestic animals from farms, abattoirs and livestock markets was examined by enzyme-linked immunosorbent assay (ELISA) for immunoglobulin G (IgG) antibodies to CCHF virus. Ticks were collected from selected animals, identified, pooled by species, host and location and tested for evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 17 publications
5
65
1
4
Order By: Relevance
“…One possible reason for the lower prevalence of infection in cattle (13.0%) could be the low frequency of pasture usage of dairy cattle in the region; however, small ruminants are continuously in the pasture during the season. In accordance with our results, similar studies (7,12,14,15,18) confirmed that the CCHF antibody prevalence is generally higher in small ruminants than cattle. Although there are no similar data from Turkey to compare the results, very limited surveys were conducted in the endemic region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One possible reason for the lower prevalence of infection in cattle (13.0%) could be the low frequency of pasture usage of dairy cattle in the region; however, small ruminants are continuously in the pasture during the season. In accordance with our results, similar studies (7,12,14,15,18) confirmed that the CCHF antibody prevalence is generally higher in small ruminants than cattle. Although there are no similar data from Turkey to compare the results, very limited surveys were conducted in the endemic region.…”
Section: Discussionsupporting
confidence: 93%
“…The overall seroprevalence rate of 33.1%, which is comparable to some previous studies (18), indicates that CCHF virus infection is moderately distributed throughout the studied population. The existence of extremely different infection rates among provinces in the same country was previously reported in Iran (3).…”
Section: Discussionsupporting
confidence: 89%
“…A serosurvey performed as part of the investigation found that many livestock animals raised in the region had antibodies to CCHFV, while imported animals were negative. Human infections were identified in Oman in the mid-1990s, and a subsequent survey of livestock and ticks confirmed the local circulation of the virus (Scrimgeour, 1996;Williams et al, 2000) …”
Section: The Middle Eastmentioning
confidence: 98%
“…CCHFV infection was first described during an outbreak in Russia during the 1940s, when more than 200 cases of severe hemorrhagic fever were reported among agricultural workers and soldiers in the Crimean peninsula (15,16). Since then, the virus has spread throughout many regions of the world, including sub-Saharan Africa (60,61), Bulgaria, the Arabian Peninsula, Iraq, Pakistan, the former Yugoslavia, northern Greece, and northwest China (16,23,(42)(43)(44)(45).…”
mentioning
confidence: 99%